The use of step aerobics and the stability ball to improve balance and quality of life in community-dwelling older adults – a randomized exploratory study. (July 2017) - Dunsky, Ayelet; Yahalom, Tal; Arnon, Michal; Lidor, Ronnie
Highlights: Fall prevention programs for elderly are of high interest among researchers. Balance improvement is a major component of fall prevention programs. Step aerobics or stability ball training are rare in fall prevention programs. Step aerobics training was found to improve balance among older adults. Stability ball/step aerobics training was found to improve health perception. Abstract: Objective: To explore the use of step aerobics (SA) and the stability ball (SB) as tools for balance improvement in community-dwelling older adults. Method: Forty-two women (age: 72.2 ± 5.8 years) who attended a community day center volunteered to participate in the study. Following the first assessment session, 28 women were assigned randomly to one of two experimental groups (the use of either SA or SB). The other 14 participants, who were engaged in a ceramic class, served as the control group. The study design was based on four assessment sessions and eight weeks of intervention. Assessment included four balance tests: Timed Up and Go (TUG), One-Leg Stand, Functional Reach, and the Performance-Oriented Assessment of Mobility (POMA). Quality of life was assessed by the use of the Short Form-36 Health Survey questionnaire. Results: The TUG and POMA intervention improved significantly ( d  = .83 and d  = .95, respectively) following the SA. In addition, general health perception following both the SA and SB interventions improved significantly relative to the control condition ( d  = .62 and d  = .22, respectively). Discussion: The findings of this study may imply that trainers should consider the inclusion of SA and SB as components of physical activity programs for seniors, aimed at improving balance ability and quality of life.